Penerapan Algoritma Fibonacci Codes Dalam Aplikasi Kompresi File Citra Digital - Rizkah Fadillah (KOMIK (Konferensi Nasional Teknologi Informasi dan Komputer), 2022)
The development of technology greatly affects the delivery of information, where previously the transmission of data could only be done with the size of the original file so that the data presented was limited and if the transmission of data and information in large quantities was needed a large storage space so that the process became slow. For example, in an image file or image in JPG format. The better the quality of the resulting image, the larger the hexa size needed to send the image, thus impacting speed and storage space. The solution to the problem is to shrink the file size with compression techniques. The compression algorithm used to compress image files in this study is Fibonacci codes. In addition to easily understanding the encoding process and the decoding process or decompression process, Fibonacci code is also very simple and effective for compressing image files. The technique done by removing some bits in the image file, there are two types of data that are compressed, namely lossy and lossless. In this study, a lossless type was used where the compressed file can be purchased as before without changing it. In the application of the Fibonacci codes, the process of compressing image files is considered very effective because it can produce a value of Compression Ratio (CR) of 62.5% and a Space Saving (Ss) value of 37.5% so that the image file after compression measuring 1,805 KB or 1.76 MB is much smaller than the original size of 2.82 MB.